The Effectiveness of Liquid Waste Originated From Biogas Processing in the Palm Oil Industry PTPN V Tandun for Chlorella sp. Biomass Production - Yolanda, Yuni; Dahril, T.; ', Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
A study has been conducted in December 2015. Different amount of waste was mixed with aquadest, there were P0 (0% waste), P1 (15% waste), P2 (20% waste) and P3 (25% waste) and the waste was used as nutrient source for the microalgae. Samplings were conducted once/ 5 days during a 20 days period. Parameters measured were the biomass of Chlorella sp., Nitrate (NO3), phosphate (PO4), BOD, pH, temperature, and TDS. Results shown that by the end of the experiment, the highest Chlorella sp. biomass production was 5.89 mg/L (in the P3). During the research, the nutrient available in the media decreased, from 18.4 to 4.3 mg/L (Nitrate) and from 1.37 to 0.32 mg/L (Phosphate), indicating that the nutrient have been used for growing the microalgae. Based on data obtained, it can be concluded that the biogas processing waste from the Palm Oil Industry is effective nutrient source for Chlorella sp.Keyword: Liquid waste of biogas Palm Oil Industry, Mirkoalgae, Chlorella sp.